ANALISIS KEBIJAKAN STOCK OPNAME DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KUBU RAYA - Widiyasari, Fitri; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study discusses thepolicy stock opname at the Archives and Library Office ofKubu Raya Regency. The purpose of the study was to describe theimplementation of thepolicy stock opname at the Archives and Library Office ofKubu Raya Regency as well as the obstacles it faced. This study uses a descriptivemethod with a qualitative approach. Collecting data by means of observation,documentation and interviews. Informants in this study are Head of Service, Headof Libraries and Librarians. The result of this research is that the Office ofArchives and Library of Kubu Raya Regency does not have apolicy stock opname.However, the implementation of the stock taking carried out in 2020 is theimplementation of the activities of the Regency/City SNP and is the librarian's ideaas the use of free time due to closing services during the covid-19 pandemic. Theinitial obstacle faced was the lack of understanding of SNP by library humanresources. So that no other library human resources are willing to work on it.Constraints in its implementation are the lack of library human resources, nofunds, inconsistent implementation time, and lack of attention to the importance ofstock taking.Keywords: Library Policy, District/City Library, Stock Opname.